Supervision of Independent Commissioners and Audit Committee on Earnings Management Practices - Supardi Supardi (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study examines the supervision of independent commissioners, audit committees, and Control Social Responsibility (CSR) disclosures on Earning Management (EM) practices in banking companies listed on the Indonesia Stock Exchange for the financial year ending December 31, 2015, to 2017. used in this study is the difference between discretionary Realized Security Gain or Loss (RSGL) and discretionary Loan Loss Provision (LLP). Data were obtained using the purposive sampling method, and data were obtained from both the IDX and the websites of each bank. The research hypotheses were tested with ordinary least squares. The results show that CSR does not affect EM. The results also show that the supervision of independent commissioners has a significant negative effect on EM and the audit committee has no effect on EM. This research is expected to contribute to the existing literature by complementing and enriching the findings of the influence of independent commissioners on earnings management.